(3eNJUQ aQOhS GdMceIs - (3Ydj Hf QHf GdWHQj, CHh GdMSf,J (B247 (3g` s ((3CjhH Hf YKeGf s)
(3ChdgG (B:s
(3GdHGH GdChd ai hGdUhQ GdcejI hGdcjajI Ydi eG bGdJ GdadGSaI hef NGdage ajg s
(3BNQgG (B:s
(3hEf Ccd MGeVkG CVQSJg hZjQ bhI CVQGSg aEf de jbHd Pdc CQSd eY GdhMhT ai GdHQ JeJ GdCHhGH GdeNJUQI ef cJGH aQOhS GdMceI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3GdfSNI HgG MhGTs
(3HgG CQHYI hKdGKhf HGHkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B288s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs